Development of Interactive Multimedia Based on Power Point at Fluid Preasure Material and Implementation in Life; for Junior High School Students - Chakra Wirangga; Yuni Ahda; Fitri Arsih (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2018)
The purposes of this research are to produce valid and practice interactive multimedia based on PowerPoint at fluid preasure material and implementation in life for SMP/MTs.students. This research used three stages of 4-D models. The subjects of this research were 23 students class VIII SMP Negeri 3 Pariaman and 2 teachers. The object of this research was interactive multimedia based on PowerPoint at fluid preasure material and implementation in life that validated by 5 validators. Data in this research was primary data collected from validity and practicality questionnaire. The result of validity was 85,94% with criteria valid, practicality by teacher and students are practice and very practice with value 88,46% from teacher and 91,71% from students.